Morpho-colorimetric characterization of the perigonium of the Alstroemeria pulchra complex (Alstroemeriaceae, Alstroemerieae) as an aid to delimit its infraspecific taxa - Villalobos, Nicolás I.; Finot, Víctor L.; Toro-Núñez, Oscar; Baeza, Carlos; Ruiz, Eduardo; Carrasco, Pedro; Campos, Jorge; Melín, Pedro (Phytotaxa, 2023)
The main taxonomic characters of Alstroemeria derive from the perianth and have traditionally been used from qualitative perspectives, which difficult their interpretation, especially in species considered as infraspecific complexes. Through spectrophotometry and specialized image analysis approaches, a total of one hundred and sixty flowers from twenty populations of the Alstroemeria pulchra complex were quantified. Our results allowed us to recognize the infraspecific taxa A. pulchra subsp. lavandulacea, A. pulchra var. maxima, and A. pulchra var. pulchra through the color, shape, size, and ornamental patterns of their tepals. The colorimetric information subjected to discriminant analysis corroborate the taxonomic utility of flower color. Similar results were obtained from the analysis of ornamental patterns, sizes, and shapes of the tepals. The discriminant analysis of the combined matrix that included the shape and ornamental patterns allowed us to identify three non-overlapping groups within A. pulchra, with a high differentiation degree. These results significantly contribute to improving the understanding of the phenotypic variability of A. pulchra and its infraspecific taxa. This information will serve as a basis for systematic studies that will address the relationships between these and other related taxa from an integrative taxonomic perspective.